Congenital Urethral Diverticulum With Stone in A 42 Year Old Male Patient: a Case Report (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2021)
Urethral diverticulum (UD) is a localised out pouching or fusiform dilatation of the urethra. UD commonly found in women and very rare in men. We present a case of 42-years old male suffered from scrotal swelling with hard consistency and lower urinary track symptom (LUTS) for more than 30 years. At first, scrotal mass was suspected as scrotal cancer. An open surgery was perfomed, and a giant stone with diverticulum was found. With limited facilities and the absence of urologist, we performed a stone removal and drainage placement before we referred the patient to urologist for definitive treatment. UD is a very rare case, especially male UD. Doctors and other health workers in rural area must remain aware of rare cases so early diagnosis can be found and further complication can be prevented.